2011
DOI: 10.1007/s00253-011-3096-7
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a new type of intracellular PHB depolymerase from Rhodospirillum rubrum with high hydrolytic activity on native PHB granules

Abstract: A Rhodospirillum rubrum gene that is predicted to code for an extracellular poly(3-hydroxybutyrate) (PHB) depolymerase by the recently published polyhydroxyalkanoates (PHA) depolymerase engineering database was cloned. The gene product (PhaZ3( Rru )) was expressed in recombinant E. coli, purified and biochemically characterized. PhaZ3( Rru ) turned out, however, to share characteristics of intracellular PHB depolymerases and revealed a combination of properties that have not yet been described for other PHB de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The physiological function of R. rubrum PHB depolymerase remains to be elucidated, since PHB granules are located intracellularly. PhaZ1 Rru is close to extracellular PHB depolymerases, according to its sequence, its putative catalytic amino acid triad, and the presence of a functional signal peptide, although it differs by its inability to hydrolyze denatured PHB, very likely due to the absence of a substrate-binding domain (25,59). As expected, the mcl-PHA depolymerase from B. bacteriovorus HD100 shares no amino acid homology with the PHB depolymerase of R. rubrum.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The physiological function of R. rubrum PHB depolymerase remains to be elucidated, since PHB granules are located intracellularly. PhaZ1 Rru is close to extracellular PHB depolymerases, according to its sequence, its putative catalytic amino acid triad, and the presence of a functional signal peptide, although it differs by its inability to hydrolyze denatured PHB, very likely due to the absence of a substrate-binding domain (25,59). As expected, the mcl-PHA depolymerase from B. bacteriovorus HD100 shares no amino acid homology with the PHB depolymerase of R. rubrum.…”
Section: Discussionmentioning
confidence: 89%
“…The depolymerases have been classified as intra-or extracellular enzymes, with the exception of the PHB depolymerase from Rhodospirillum rubrum (PhaZ1 Rru ), which is located in the periplasm (25,59). The physiological function of R. rubrum PHB depolymerase remains to be elucidated, since PHB granules are located intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Subcellular localization of PhaZd1 and PhaZd2. If the physiological function of PhaZd1 and PhaZd2 is the depolymerization of accumulated PHB, the enzymes should be able to specifically bind to PHB in vivo, as has been previously described for other iPHB depolymerases (22,44). Attachment to and detachment from PHB granules of proteins with a PHB depolymerase function could be a way to regulate the accumulation and mobilization of accumulated PHB.…”
Section: Resultsmentioning
confidence: 99%
“…PhaZ1 was shown to be located in the cell's periplasm and is unlikely physically involved in in vivo polyhydroxybutyrate (PHB) degradation (20). In vitro studies on the gene product of phaZ3 showed that this PHA depolymerase was specific for amorphous PHA SCL but was predicted to be inactive at cytoplasm-typical concentrations of divalent cations, such as Mg 2ϩ (32). In contrast, PhaZ2 shows significant homologies to the well-characterized intracellular PHA SCL depolymerase of Ralstonia eutropha (PhaZ1) and was therefore predicted to be responsible for intracellular PHA degradation in R. rubrum (20,32,33).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies on the gene product of phaZ3 showed that this PHA depolymerase was specific for amorphous PHA SCL but was predicted to be inactive at cytoplasm-typical concentrations of divalent cations, such as Mg 2ϩ (32). In contrast, PhaZ2 shows significant homologies to the well-characterized intracellular PHA SCL depolymerase of Ralstonia eutropha (PhaZ1) and was therefore predicted to be responsible for intracellular PHA degradation in R. rubrum (20,32,33). Thus, phaZ2 (locus tag Rru_A3356) was chosen for (i) deletion in R. rubrum ⌬phaC1 ⌬phaC2, as well as (ii) site-directed mutagenesis leading to an amino acid exchange in the putative active site of PhaZ2.…”
Section: Resultsmentioning
confidence: 99%